Faktor-faktor Yang Mempengaruhi Pendapatan Usaha Penggemukan Sapi (Kasus di Kelurahan Ekajaya, Kecamatan Jambi Selatan Kotamadya Jambi) - Mulyana, Sambas (Fakultas Peternakan Universitas Jambi, 2009)
A research was conducted to determine the influence of cost of sapi bakalan, cost of labour, cost of cage depreciation, and cost of cage equipment to income of farmer, in Kelurahan Ekajaya, Kecamatan Jambi Selatan, Jambi Regency. Research was done through survey. Thirty household of farmer keep cow as fattening object were unit of the research drawn by simple random sampling. Data was analyzed by descriptive method and Multiple regression. Result of this study showed that cost of sapi bakalan Rp.3.360.000 (57,36%), cost of labour Rp.2.000.000, cost of cage depreciation Rp.450.000 (7,68%), and cost of cage equipment Rp.48.000 (0,82%), totally Rp.5.858.000. Revenue comes from value of cow was sold Rp.10.530.000, so the farmer income was Rp.4.642.000. Simultaneously cost of sapi bakalan, cost of labour, cost of cage depreciation, and cost of cage equipment , influences the farmer income, and partially cost of sapi bakalan and cost of labour significantly influence farmer income.